Implementation and Challenges of Financial Management at Universitas Almuslim in Supporting Quality Education: A Qualitative Study of Funding Sources and Budget Allocation - Sonny Muhammad Ikhsan Mangkuwinata; Haryani; Denny Sumantri Mangkuwinata (JURNAL ILMIAH GEMA PERENCANA, 2026)
Financial management plays a strategic role in ensuring the sustainability and quality of higher education institutions, particularly private universities operating under limited financial capacity. This study aims to examine the implementation and challenges of financial management at Universitas Almuslim in supporting quality education, with a specific focus on funding sources and budget allocation practices. Employing a qualitative case study design, data were collected through in-depth interviews with university leaders, financial administrators, and academic managers, complemented by an analysis of institutional financial documents. The data were analyzed thematically using the framework proposed by Miles, Huberman, and Saldaña. The findings reveal that Universitas Almuslim relies predominantly on internal funding, especially student tuition fees, while external funding remains limited and non-sustainable. Budget allocation is primarily directed toward routine academic operations, leaving restricted fiscal space for long-term quality enhancement initiatives. Key challenges include high dependency on tuition-based funding, limited budget flexibility, and vulnerability to fluctuations in student enrolment. Despite these constraints, the institution adopts adaptive strategies such as prioritizing core academic activities and optimizing available resources to maintain educational quality. These findings highlight the importance of strengthening transparent, flexible, and context-responsive financial governance to support sustainable quality development in private higher education institutions.